The Article Personification of Natural Elemens Tsuki (月) and Tori (鳥) in 4 Kalafina Songs - Rita Susanti; Wisnu Wardani; Riva Amdana (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2025)
Some people, songs are a way to cheer up when they feel anxious and sad. However, there are also those who use songs as an expression of happiness. Lyrics in songs are basically created by songwriters to represent the current situation or events. Likewise in Japanese songs. In addition to representing this, songwriters in Japan often include natural elements in the lyrics of the songs they create, because for Japanese people, nature and its phenomena are representatives of God. Therefore, this study raises the form of personification that appears in songs related to nature, especially tsuki 'moon' and tori 'bird' in the lyrics of a Japanese female band called Kalafina. The aim is to describe the meaning of personification related to nature and the function of this personification. Qualitative methods with listening and recording techniques are tools for collecting data.Based on the results of data analysis on 4 song titles with 4 personifications, it can be seen that birds are a symbol for songwriters to think about the steps forward that someone wants to achieve, considering that birds will fly high and away. Meanwhile, the moon is a symbol to express someone's desire for beauty.